Shastry-Sutherland phase formation in magnetically frustrated Ce2Pd2In1-xSnx alloys - Sereni, Julian Gustavo Renzo; Roberts, J.; Gastaldo, F.; Berisso, M. G.; Giovannini, M. (Elsevier, 2019)
Fil: Sereni, Julian Gustavo Renzo. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina